Design ofan UASB system and stabilization ponds for wastewater treatment from a shrimp processing industry - Pérez, Jhonny; Fernández, Nola; Herrera, Mario; Galindo, Andrés; Toncel, Enrique; Rojano, Roberto; Daza, Sammy (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Véase archivo PDF